La stips des Alpes à la Méditerranée : interpréter la présence des monnaies dans les sanctuaires d’époque romaine - Raphaël Golosetti (Gallia)
This contribution explores first of all the contexts of coins in Roman sanctuaries, in a study area where monetary offerings exist from the 5th c. BC onwards for southern Gaul (Correns, Var), from at least La Tène C2 in the Alps (Grand-Saint-Bernard, Hautes-Alpes), with the exception of stipes in water, which could be characterized as late and Roman. Several contexts demonstrate “sacred” monetary hoards, i.e., with a certain inalienability, at least in practice, if not by law. In the same way, coins found in sources never seem to have been retrieved. Furthermore, only the latter context enables archaeology to confirm the reality of iactatio stipis. This cannot be ruled out for “terrestrial” contexts, but our study attempts to demonstrate that other hypotheses, also documented by antique texts, can explain the presence of coins on sanctuary floors. In our opinion, part of these (the majority) appear to come from the simple dispersal of coins on gallery floors in the “fana” or passageway zones of sanctuaries, in particular during collection box levies, from containers, or from the tables and altars on which they were placed. Based on several clear contexts, we suggest that other types of stipes containers may have been in use, in perishable materials or in pottery, and that the deterioration/retrieval of these containers could account for the dispersal of coins on the floors of places of worship. Other contexts show different forms of practices linked to coins: for example, a tiny percentage of coins ended up in characteristic foundation hoard pits, possibly linked to cult worship or hoards of construction offerings. In other cases, the coins were, more simply, found in a deposit.For the coins themselves, it is important to underline that a single case of ritual manipulation (Coin de la Ville, in Martigny) is recorded for the Roman period. This is extremely interesting as it signifies the end of the practice of coin perforation, which was well identified for the south of Gaul in the Iron Age, during the Roman period. Finally, bibliographic data emphasize the constant values of the deposited coins, the most common coins, or often, but not exclusively, those of the least value. This result is not surprising and is in keeping with the pattern in northern Gaul and eastern Gaul. This question of the relationship between money in sanctuaries and monetary circulation also highlights the risks of basing considerations of sanctuary attendance on the analysis of the evolution of the number of coins per period. With the exception of coins thrown into sources, which are difficult to retrieve, coins should not be used to evaluate the attendance of places of worship. The numismatic study by A. Geiser on the sanctuary of En Zibre in Martigny (Switzerland) allows us, for example, to show to what extent the observed evolution of the number of monetary offerings was characteristic of monetary circulation in the whole agglomeration of Martigny. Based on other occurrences (Faverges, La Bâtie-Montsaléons, Hautes-Alpes), we attempted to demonstrate that the poor representation of coins in the early Roman Empire does not indicate low attendance, but is rather the result of the regular cleaning of sanctuaries, which affected the representativity of coins for the earliest periods. The clear disparity between the image portrayed by the coins and the construction phases of these places of worship can only confirm this vision. At the same time, the important quantity of coins in several sanctuaries, some of which are clearly public, demonstrates that some of the coins from the 4th to the beginning of the 5th c. are linked to worship activities and not to losses during recovery operations.